Mathematical Modeling & Engineering Design of Wastewater Treatment Unit for Al-Kut Gas Filling Company - Khaleel, Omar M.; Dawood, Maan M.; Mohammed, Harith A.; Jameel , Zeena I. (Journal of Petroleum Research and Studies, 2022)
New talented treatment method without chemicals and with minimum operational cost was performed to treat industrial waste water discharged by a hydrostatic test performed on the gas bottles maintenance workshops to reuse it. A common method by Tarleton and Wakeman was used to select the general treatment philosophy, The implementation of this study was carried out on three stages, water sample analysis, simulates the proposed preliminary design and detailed engineering designing for the first stage, a sample of waste water was brought from Al-Kut Gas Filling Company - maintenance section and tested for settling, aeration, and filtration. The experiments showed that the most of sediments were insoluble but rather than suspended in water and can be removed by settling. Furthermore, aeration test showed that concentrated Thiophene odor in water was removed at 50 C of water with diffused air bubbling. On the other hand, filtration of using 10 Micron filter paper was achieved to eliminate the rest of tiny sedimentation. Secondly, general dimension of equipment was calculated by engineering design equation according to qualitative and quantitative analyses of waste water. Accordingly, a set of experiments of simulation using ANSYS V19.0 and Eulerian – Eulerian as mathematical model were performed for the 3D two phase flow sedimentation tank with capacity of 5 m3/hr to find the optimum sedimentation performance by testing of the modifications on the tank geometry (baffle depth, distance between baffle and inlet, hooper). Simulation results showed that the optimum tank geometry (0.86 m Baffle depth with inclined part, 2.5m distance between baffle and inlet, hooper within V type geometry W=1.67m/0.29 m, D=1.03 m and tank dimension (L=10m, W=2.5, H=2.5 with slope angle = 2o) with 49.5 volume % in sediment layer with a minimum sediment layer height. The third stage included an accomplishment of the Preliminary and detailed engineering design of the entire unit by SOLIDWORKS software to be ready for prototyping.